Effect of Preoperative Anti Tuberculosis Drug Administration Duration on Tuberculous Spondylitis Surgical Treatment Outcomes (Jurnal Anestesi Perioperatif, 2020)
Preoperative anti-tuberculosis (TB) drugs play a role in surgery of TB spondylitis patients to prevent transmission in the operating room, reduce inflammatory processes and prevent relapse. Currently, there is no study on effects of preoperative anti TB drugs administration duration on the spinal TB patients surgical outcome at Dr. Hasan Sadikin Hospital (RSHS). This study used retrospective method by analyzing medical record data of TB spondylitis patients operated at RSHS, January 2014–May 2018. Based on the preoperative TB drugs duration, patients were divided into 2 groups: preoperative TB drugs group
Keywords: C-reactive protein (CRP); erythrocyte sedimentation rate (ESR); preoperative TB drugs